PROBLEMATIKA PEMILIHAN MATERI MUFRODAT MENURUT PERSPEKTIF RUSYDI AHMAD THU’AIMAH - Kholidun Asri (Universitas Islam Negeri Mataram, 2020)
The aim of this study is therefore to identify the types of problemsof teachers in the selection of Arabic mufrodat in Grade VII students ofMadrasah Tsanawiyah Fadllillah. The method used in this research, usingresearch and development methods (R&D) refers to the Thiagarajan 4Dmodel, which focuses on the definition or definition phase, using the RusydiAhmad Thu’aimah mufrodat selection principle, which is divided into sevenmufrodat selection principles. This research was carried out at one of the mostcumbersome educational institutions in the Waru area , at MTs. Fadllillah Jl.Kyai Ali No 57 A Sidoarjo Waru Sidoarjo. The results of this study have ledto the discovery of many of the problems faced by teachers in determininggood, accurate and effective mufrodats to be taught to students. For example,the appropriateness of the principles for the selection of mufrodat accordingto the principle of frequency is the choice of mufrodat in accordance withthe application of everyday language, but there are also principles that arenot appropriate, such as the principle of availability of teachers who do notknow the ability of students to understand words.